THE DEVELOPMENT OF THEMATIC – INTEGRATED E-PORTFOLIO MEDIA WEB BLOG BASED TO INCREASE THE SCIENTIFIC LITERACY OF ELEMENTARY TEACHER EDUCATION PROGRAM’S STUDENT (Jurnal Pendidikan IPA Indonesia, 2016)
The aim of this study is to improve the scientific literacy of Elementary Teacher Education Program’s students using a valid thematic-integrated e-portfolio media web blog based. Applied research and development methods for elementary school’s course planning by applying thematic-integrated e-portfolio media web blog based. The result of media and evaluation experts recommend that e-portfolio which has been developed gets 98.75% of eligibility percentage which means that it is very decent to be used in the lecturing.  Thematic-Integrated e-portfolio media web blog based effectively improves the scientific literacy of students to reach multidimensional level, in which students are able to take advantage of various concepts and demonstrate the ability to connect these concepts to daily life.  Students understand how science, society and technology are interrelated and influence each other. Students also demonstrate an understanding of the nature of science through his answer.